(untitled) (Security Dialogues, 2024)
Migrations, as a global contemporary phenomenon, take place as a result of various “push-pull factors”, and can have many political, social, cultural or security implications. However, we can state that it is mostly about voluntary migration, while on the other hand, wars as a “push factor” of migration mostly cause forced migration. The war in Ukraine triggered the largest migration movements in Europe after World War II, because according to UNHCR data, 4.8 million refugees from Ukraine were registered for temporary protection or similar programs in the European Union (EU). However, the question arises as to what types of migrations the war in Ukraine triggered, were actually only Ukrainians moving, or as a result of the war were movements of citizens of the Russian Federation recorded as well? The purpose of this paper is to look at the approach of the EU to the war in Ukraine from several different perspectives, the approach of the countries of the Western Balkans (WB), as well as the approach of Bosnia and Herzegovina (BiH). The paper will present the scope of the migration implications of the war in Ukraine on Bosnia and Herzegovina, through the presentation of data on the entry, movement, stay and international protection of citizens of Ukraine and citizens of the Russian Federation in Bosnia and Herzegovina. Special focus will be on the analysis of the reasons for these migrations, and the approach to solving their status will be considered.